2007
DOI: 10.1002/uog.3958
|View full text |Cite
|
Sign up to set email alerts
|

Pleural and pericardial effusion: a potential ultrasonographic marker for the prenatal differential diagnosis between congenital diaphragmatic eventration and congenital diaphragmatic hernia

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 114 publications
(199 reference statements)
0
12
0
Order By: Relevance
“…Finally, intrafetal fluid effusions are a relatively common ultrasound finding in CDH fetuses, observed in up to 5% and 29% of left‐ and right‐sided CDH cases, respectively . Such effusions could be related to liver congestion due to hepatic venous kinking, or to bowel irritation . However, it has been shown that CDH fetuses with associated pleural effusion/ascites have the same postnatal outcome as those with isolated CDH without those effusions .…”
Section: Additional Testingmentioning
confidence: 99%
“…Finally, intrafetal fluid effusions are a relatively common ultrasound finding in CDH fetuses, observed in up to 5% and 29% of left‐ and right‐sided CDH cases, respectively . Such effusions could be related to liver congestion due to hepatic venous kinking, or to bowel irritation . However, it has been shown that CDH fetuses with associated pleural effusion/ascites have the same postnatal outcome as those with isolated CDH without those effusions .…”
Section: Additional Testingmentioning
confidence: 99%
“…Diaphragmatic eventration, characterised by defective diaphragmatic muscularisation, can be challenging to differentiate from CDH antenatally. The former shows a cephalic displacement of the diaphragm and is often associated with pleural and/or pericardial effusion [22]. Pathologies associated with CDH include cardiac, renal, central nervous system and gastrointestinal anomalies [23].…”
Section: Imaging Modalities For Cdhmentioning
confidence: 99%
“…The former shows a cephalic displacement of the diaphragm and is often associated with pleural and/or pericardial effusion ( fig. 5 ) [21] . Distinction between these two entities is important, because of the better prognosis and different management of diaphragmatic eventration.…”
Section: Differential Diagnosis and Associated Anomaliesmentioning
confidence: 99%